The association between short-term exposure to ambient PM2.5 and hospitalization costs in patients with myocardial infarction: a hospital-based study. - Wang, Liang-Mei; Wang, Ke-Xue; Guo, Yuan-Lin; Yang, Li-Li; Liu, Hao; Zhou, Yu-Meng; Li, Da-Wei; Zhou, Chun-Bei; Liu, Xiao-Ling; Yao, Chun-Yan; Long, Jin-Yun; Li, Xiu-Kuan; et al. (International Journal of Environmental Health Research, 2025)
Myocardial infarction (MI) ranks as one of the primary causes of global disabilities and disease deaths. The association between fine particulate matter (PM2.5) and MI has gained attention in recent years. In this study, we assessed the relationship between short-term PM2.5 exposure and MI inpatient hospitalization costs using multiple linear regression, and estimated the attributable MI burden. Stratified analyses were done by gender, age, season, and hyperlipidemia. The economic burden of PM2.5 was assessed using WHO (25 μg/m³) and China's (75 μg/m³) criteria. PM2.5 concentration positively correlated with MI hospitalization costs. A 10 μg/m³ increase in Lag015 PM2.5 led to a 940.05 CNY (95% CI: 141.87–1463.23) increase in costs. Furthermore, the association was stronger in males, those <65 years old, and patients with hyperlipidemia. This study first indicates that short-term PM2.5 levels can be positively associated with MI's economic burden, especially in cool seasons.